New species of Ablabesmyia Johannsen from the Neotropical region: First report of a sponge-dwelling Tanypodinae - Fusari, Lívia Maria; Oliveira, Caroline S.Neubern; Hamada, Neusa; Roque, Fabio O. (Zootaxa, 2012)
The larva, pupa and male of a new Neotropical chironomid species, Ablabesmyia tucuxi Neubern et Fusari sp. n., are described and illustrated. The larvae were found in freshwater sponge colonies of Drulia uruguayensis Bonetto et Ezcurra de Drago, 1968 and Oncosclera spinifera (Bonetto et Ezcurra de Drago, 1973) in Brazilian savanna streams. The morphological characteristics of the larval head and the presence of fine particles in the larval gut contents suggest that the larvae probably feed on the sponge tissue or on other animals that live inside the sponges. © 2012 Magnolia Press.
Keywords: Ablabesmyia; Animalsia; Chironomidae; Diptera; Drulia; Hexapoda; Oncosclera; Sotalia Fluviatilis; Spongillidae; Tanypodinae